Working memory interventions via physical activity and ICTs: A strategic issue for the improvement of school students' learning performance - Angelopoulou, Effrosyni; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
Nowadays, there is a great need for schools to be transformed into more innovative learning environments with more innovative approaches to learning and teaching so as students to be allowed to develop their various skills and abilities to their fullest extent. Therefore, we present the role of physical activity and ICT-based interventions for working memory enhancement as a strategic issue for the improvement of students’ learning outcomes. According to research findings, multi-component exercise and ICT-based intervention programs can significantly contribute to the improvement of children’s and adolescents’ working memory and thus can have a positive effect on children’s and adolescents’ learning performance. Finally, this paper could trigger educators and policy-makers towards the ideal planning of innovative multi-component physical activity and ICT-based intervention programs and their incorporation into the school curriculum aiming at the working memory enhancement in children and adolescents and the improvement of their learning outcomes